LIVES co-organizes world milk day celebration in Hawassa - International Livestock Research Institute (International Livestock Research Institute, 2014)
This World milk day celebration in Hawassa was jointly organized by the Regional Bureau of Agriculture, Agricultural Growth Program-Livestock Market Development (AGP-LMD) project of USAID, Livestock and Irrigation Value Chains for Ethiopian Smallholders (LIVES) project of ILRI (International Livestock Research Institute) and SNV-EDGET project. [This video is recorded by Ethiopian Broadcasting Corporation (EBC)–Debub television program] – June 30, 2014